Cultivating Resilience and Success: Support Systems for Novice Teachers in Diverse Contexts - Alkhansaa Diab; Edna Green (MDPI AG, 2024)
This qualitative study explores the support systems that foster resilience and success among novice teachers in diverse sociocultural contexts within Israeli teacher training colleges. Semistructured interviews were conducted with a sample of 51 novice teachers from various educational backgrounds. The findings reveal a complex network of support encompassing formal institutional structures, such as mentorship programs and induction workshops, as well as informal networks of familial support and cultural connections. Utilizing a holistic framework that integrates social support theory, social connection theory, and self-determination theory, the study highlights the interplay between external support and novice teachers' intrinsic motivations, which drive their pursuit of autonomy, competence, and relatedness. The key findings underscore the crucial role of comprehensive induction and mentoring programs that address novice teachers' emotional, psychological, and professional needs. These programs should provide emotional support, opportunities for collaboration and peer learning, and personalized guidance from experienced mentors. The study also emphasizes the significance of supportive school cultures, meaningful mentoring relationships, and the strength of informal support networks in promoting novice teachers' well-being and effectiveness. The implications of this research are far-reaching, offering valuable insights for the global educational community on developing supportive ecosystems that enhance novice teachers' resilience, job satisfaction, and retention rates. By articulating the essential role of both formal and informal support systems, this study contributes significantly to the discourse on teacher education and addresses a crucial gap in the literature on support mechanisms across diverse educational settings.